Face it or hide it: parental socialization of reappraisal and response suppression - Gunzenhauser, Catherine; Faesche, Anika; Friedlmeier, Wolfgang; von Suchodoletz, Antje (Frontiers in Psychology, 2014)
Mastery of cognitive emotion regulation strategies is an important developmental task. This paper focuses on two strategies that occur from preschool age onwards (Stegge & Meerum Terwogt, 2007): reappraisal and response suppression. Parental socialization of these strategies was investigated in a sample of N = 219 parents and their children. Informed by the tripartite model of family impact on children’s emotion regulation, direct relations of emotion socialization components (modeling and reactions to the child’s negative emotions) and indirect relations of parental emotion-related beliefs (such as parental emotion regulation self-efficacy) were examined. Data on emotion socialization components and parental beliefs on emotion regulation were collected via self-report. Data on children’s emotion regulation strategies were collected via parent report. Findings showed direct effects of parental modeling and parenting practices on children’s emotion regulation strategies, with distinct socialization paths for reappraisal and response suppression. An indirect effect of parental emotion regulation self-efficacy on children’s reappraisal was found. These associations were not moderated by parent sex. Findings highlight the importance of both socialization components and parental emotion-related beliefs for the socialization of cognitive emotion regulation strategies and suggest a domain-specific approach to the socialization of emotion regulation strategies.